Synovial Chondromatosis of the Temporomandibular Joint (TMJ): A case report (Research, Society and Development, 2024)
Synovial Chondromatosis (CS) is a benign condition characterized by the formation of metaplastic cartilage in the synovial membrane of the joint, resulting in numerous osteocartilaginous bodies that may be attached or not, predominantly found in the intra-articular space, can also be found in regions extra-articular. CS mainly affects the large synovial joints, especially the knee, hip, elbow, and ankle, while Temporomandibular Joint (TMJ) involvement is rare. This article aims to show that excision through open surgery of the TMJ is a safe, aesthetically favorable option, free from recurrence, if planned and performed correctly. Here we present a case of CS of the TMJ, diagnosed by clinical signs and symptoms associated with facial Computed Tomography and Magnetic Resonance Imaging examinations of the TMJ and treatment through open surgical excision. The clinical case shows how open surgery contributes to the direct removal of osteochondral bodies, allowing complete excision of the CS safely, and with a low incidence of motor, sensory, and aesthetic sequelae for the patient. No recurrence to date.